A numerical simulation of acoustic field within liquids subject to three orthogonal ultrasounds - Zhai, W.; Liu, H.M.; Hong, Z.Y.; Xie, W.J.; Wei, B. (Ultrasonics sonochemistry, 2017)
•Acoustic field distribution induced by 1D, 2D and 3D ultrasounds is calculated.•Sound pressure and acoustic energy density are enhanced by 3D orthogonal ultrasounds.•3D orthogonal ultrasounds effectively extends cavitation volume within liquids.•A three dimensional ultrasonic methodology is proposed to fabricate materials. When one beam of ultrasound propagates along a single direction in liquids, the cavitation effect is always confined to a limited volume close to the ultrasonic source. This greatly limits the application of power ultrasound in liquid processing and materials fabrication. In this study, a methodology for applying three orthogonal ultrasounds within liquids has been proposed. By solving the Helmholtz equation, the sound field distribution characteristics are investigated in 1D (one dimensional), 2D (two dimensional) and 3D (three dimensional) ultrasounds at their resonant frequencies, which show that the coherent interaction of three beams of ultrasounds is able to strikingly promote the sound pressure level and reinforce the mean acoustic energy density as compared with that in 1D case. Hence, the potential cavitation volume is enlarged remarkably. This opens new possibilities for the design and optimization of ultrasonic technology in fabricating materials.